2004
DOI: 10.1111/j.1601-5223.2000.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis of Epicauta Atomavia (Meloidae) and Palembus Dermestoides (Tenebrionidae) with Xyp Sex Determination System Using Standard Staining, C-Bands, NOR and Synaptonemal Complex Microspreading Techniques

Abstract: The mitotic and meiotic chromosomes of the beetles Epicautu atomaria (Meloidae) and Palembus dermestoides (Tenebrionidae) were analysed using standard staining, C-banding and silver impregnation techniques. We determine the diploid and haploid chromosome numbers, the sex determination system and describe the chromosomal morphology, the C-banding pattern and the chromosome(s) bearing NORs (nucleolar organizer regions). Both species shown 2n = 20 chromosomes, the chromosomal meioformula 9 + Xy,, and regular chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 16 publications
(24 reference statements)
4
34
0
Order By: Relevance
“…This same pattern was also observed in the autosomal chromosomes of Coleoptera (Virkki, 1983, Schneider et al, 2006Mello et al, 2014). In the sex chromosomes, the heterochromatin can extend to all chromosome arms or is restricted exclusively in the pericentromeric region (Almeida et al, 2000;Rozek et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
“…This same pattern was also observed in the autosomal chromosomes of Coleoptera (Virkki, 1983, Schneider et al, 2006Mello et al, 2014). In the sex chromosomes, the heterochromatin can extend to all chromosome arms or is restricted exclusively in the pericentromeric region (Almeida et al, 2000;Rozek et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
“…According to previous reports, in addition to pericentromeric C-bands, distal C-bands were also observed in the tenebrionids Misolampus goudoti (Juan and Petitpierre, 1989) and Palembus dermestoides (Almeida et al, 2000), while exclusively telomeric blocks were observed in the carabid Bembidion minimum (Rozek and Rudek, 1992). The additional C-bands in these beetles and in D. mimas and I. inhiata probably arose by small tandem duplications, as proposed by King and John (1980).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as observed in Z. aff. confusus, the presence of euchromatic y has been described in Gymnopleurus sturmi (Scarabaeidae), Palembus dermestoides (Tenebrionidae), Epicauta atomaria (Meloidae), and in 23 of the 25 studied species of Pimelia (Tenebrionidae) (Almeida et al, 2000;Colomba et al, 2000;Pons, 2004). In these species, the lack of labeling can be due to the minuscule size of the CH blocks in the yp.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal morphology is generally metacentric and submetacentric, with chromosomes having similar sizes, which renders the identification of individual species difficult (Petitpierre, 1996). Some studies have focused on the distribution and base pair composition of the constitutive heterochromatin in the karyotypes of Tenebrionidae species (Juan and Petitpierre, 1989;Almeida et al, 2000;Pons, 2004). In general, the heterochromatin has a pericentromeric location and accounts for about 50% of the genome and constitutes monomeric sequences with varying sizes of 100-360 base pairs (Mestrovic et al, 2000).…”
Section: Introductionmentioning
confidence: 99%